Losses, heating in tank covers of transformers - Basova, A.V.; Ivankov, V.F.; Khimiuk, I.V. (Технічна електродинаміка, 2013)
The main approaches to analytical estimations and three-dimensional modeling by finite element method of electromagnetic and thermal processes in the tank covers using ANSYS software are presented. The results of an investigation of three-dimensional constructions of tank covers of three-phase transformers taking into account not only the magnetic fields in taps, but also the leakage fields in windings, are provided. Представлено основні підходи до аналітичних оцінок і тривимірного моделювання методом скінчених елементів електромагнітних і теплових процесів в областях кришок бака з використанням програмного забезпечення ANSYS. Наведено результати досліджень тривимірних конструкцій кришок баків трифазних трансформаторів, що враховують не лише магнітні поля відведень, але і поля розсіювання обмоток Представлены основные подходы к аналитическим оценкам и трехмерному моделированию методом конечных элементов электромагнитных и тепловых процессов в областях крышек бака с использованием программного обеспечения ANSYS. Приведены результаты исследований трехмерных конструкций крышек баков трехфазных трансформаторов, учитывающих не только магнитные поля отводов, но и поля рассеивания обмоток